Manajemen Organisasi Pendidikan di SMA Negeri 1 Tebing Tinggi - Afifah, Dessy Tri; Fitri, Dira Zahara; Akbar, Faisal; Dmk, Rizki Ramadhan; Bancin, Wahdaniati; Nasution, Inom (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This research aims to determine the management of educational organizations at SMA Negeri 1 Tebingtinggi. This type of research is descriptive research with qualitative research methods. The instrument used was teacher interviews at SMA Negeri 1 Tebingtinggi. The results of the research conducted show that the management of educational organizations at SMA Negeri 1 Tebingtinggi plays a very important role for educational organizations at the school, including guidance and counseling teachers, subject teachers, homeroom teachers and other school staff.